Relationship of Family Support With Motivation For Cataract Surgery In Cataract Patients - Jajuk Winarni; Dewi Retno Puspitosari; Agus Priyanto (Universitas Pahlawan Tuanku Tambusai, 2020)
Cataract is an eye disorder in the form of clouding of the lens. Cataracts can cause blindness. One of the treatments for chest cataracts is eye lens replacement surgery. Some patients are not willing to undergo surgery because of lack of motivation. Family as the closest people have an important role in providing support to patients in undergoing therapy. The aim of this research is to determine the relationship between family support and motivation for cataract surgery in cataract clients at Undaan Eye Hospital, Surabaya. This research is a descriptive analytical study with a cross sectional approach . The population of this study was 36 clients. The sample was 36, taken using total sampling technique. The instruments in this study used research results showing that 50% of patients had high family support, 50% of patients had strong motivation to undergo cataract surgery. Correlation analysis using the Spearman rank test (p) obtained a value of P= 0.000 (<0.05), so Ha accepted and Ho rejected, meaning there is a relationship between family support and motivation for cataract surgery. The correlation coefficient value = 0.644, meaning it has a strong level of relationship. Based on the results of the research above, health workers should provide education to families to provide support to patients who will undergo cataract surgery.